Game AI pro 360. Guide to tactics and strategy - Rabin, Steve (Boca Raton : CRC Press, 2019)
"Cutting-edge tactics and strategy for game AI primarily from game developers of shipped commercial games. The book acts as a toolbox of techniques that can be applied to many common and not-so-common situations"--
Tactical position selection: an architecture and query language / Matthew Jack -- Tactical pathfinding on a NavMesh / Daniel Brewer -- Beyond the kung-fu circle: a flexible system for managing NPC attacks / Michael Dawe -- Hierarchical AI for multiplayer bots in Killzone 3 / Remco Straatman, Tim Verweij, Alex Champandard, Robert Morcus, Hylke Kleve -- Using neural networks to control agent threat response / Michael Robbins -- Looking for trouble : making NPCs search realistically / Rich Welsh -- Modeling perception and awareness in Tom Clancy's Splinter cell blacklist / Martin Walsh -- Escaping the grid : infinite-resolution influence mapping / Mike Lewis -- Modular tactical influence maps / Dave Mark -- Spatial reasoning for strategic decision making / Kevin Dill -- Extending the spatial coverage of a voxel-based navigation mesh / Kevin A. Kirst -- Being where it counts : telling paragon bots where to go / Mieszko Zieliński -- Combat outcome prediction for real-time strategy games / Marius Stanescu, Nicolas A. Barriga, and Michael Buro -- Guide to effective auto-generated spatial queries / Eric Johnson -- The role of time in spatio-temporal reasoning : three examples from Tower defense / Baylor Wetzel and Kyle Anderson -- Pitfalls and solutions when using Monte-Carlo tree search for strategy and tactical games / Gijs-Jan Roelofs -- Petri nets and AI arbitration Sergio / Ocio Barriale -- Hierarchical portfolio search in Prismata / David Churchill and Michael Buro.
OCLC-licensed vendor bibliographic record.
Keywords: Computer games -- Design; Computer games -- Programming; Artificial intelligence; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design